Germinación y sobrevivencia de las especies forestales Colubrina arborescens (Mill.) Sarg. (caoba de montaña) y Triplaris cumingiana Fisch. & C.A. Mey (Fernan Sánchez) con tres sustratos, a nivel de vivero en el cantón Buena Fe, provincia de los Ríos. - Morales Zambrano, Jeilyn Dayanara (2021)
The present research project aims to evaluate germination and survival of the forest species Colubrina arborescens (Mill.) Sarg and Triplaris cumingiana Fisch. & C.A. Mey with three substrates, the same that was carried out on the farm of Mr. Amadeo Espinoza, located in the Las Coronas area of the Buena Fe canton, Los Ríos province. For this experiment a Completely Random Design was used, in a factorial arrangement of 3 (substrates) x 2 (species), with four repetitions, three substrates were elaborated, which were: S1 (60% sown land + 20% sawdust fine + 20% river sand), S2 (40% sand + 20% sown land + 40% rice husk), S3 (100% sowed land), the germination percentage and survival data; and for the registration of the data of the variables height, diameter and number of leaves of the seedlings, it was carried out using the field forms. For the percentage of germination and survival, 25 seeds were sown for each experimental unit; with a total of 300 seeds for each species. And for the measurements of the variables of height, diameter and number of leaves, only 11 seedlings were considered, after obtaining the data, the comparison of means of interactions was carried out, it was carried out with the Tukey test (p <0.05) using the software InfoStat. The study provided the following results: for the germination percentage the C. arborescens species the best result was obtained by the substrate S1 with 90%, and for the species T. cumingiana the substrate S1 with 93% germination. For both species, the survival percentage of the substrate S3 registered the best result, with 82.76% for C. arborescens and 86.81% for the species T. cumingiana. In the variables: height, diameter and number of leaves, the species C. arborescens, the substrate S3 presented the best average in height of 10.93 cm, in an average diameter of 3.06 mm and an average of 9 leaves. Regarding the T. cumingiana species, the best average was obtained from the S1 substrate, with an average height of 23.95 cm, an average diameter of 3.61 mm and an average of 10 leaves. Keywords: Development, Growth, Dasometric, Pre-germination.